2012
DOI: 10.3889/mjms.1857-5773.2011.0202
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of Medical Students in Nigerian Universities about the Use of Plastinated Specimens for Anatomical Studies

Abstract: Over the past decade, the role of anatomical teaching in the undergraduate medical curriculum has changed considerably. At some medical schools, active dissection of cadaveric specimens is gradually being replaced by prosection-based methods and other resources such as e-learning, use of plastinated materials and models. Academic faculties in some of our medical schools are recently obtaining necessary skills in plastination technology which would aid in the future production and usage of plastinated prosectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The general acceptability of plastination as a necessary anatomical tool by teachers of anatomy in the various medical schools sampled also agrees with our previous studies, which showed that medical students where strongly in support of the introduction of plastinated specimens to complement cadaveric materials and introduce a new dimension to anatomical study (Azu et al 2012).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The general acceptability of plastination as a necessary anatomical tool by teachers of anatomy in the various medical schools sampled also agrees with our previous studies, which showed that medical students where strongly in support of the introduction of plastinated specimens to complement cadaveric materials and introduce a new dimension to anatomical study (Azu et al 2012).…”
Section: Discussionsupporting
confidence: 76%
“…This has placed an enormous burden on medical teachers and educators to adapt to the change in medical trends and to develop ways of delivering knowledge to students in a manner that are evidencebased and theoretically robust. We previously carried out a survey on the applicability and relevance of problem-based learning in anatomy for pharmacy students (Azu & Osinubi 2011) and on the introduction and relevance of plastinates in anatomical resource centres (Azu et al 2012) as part of this changing trend in medical education. Therefore, it has become more pertinent than ever to ask the question: what are the opinions of teachers of anatomy regarding the need to adapt to the newer teaching modalities such as the ProblemBased Learning method, use of plastinated specimens, computer-aided software and so forth, to teaching the subject of anatomy within the framework of the various institutions?…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…70% of the students in Nigeria and 98.23% of the students in India had no knowledge on plastination. [6,7] In this study, the rate of students who had no knowledge on Table 3 Views of students on the education provided with plastinated cadavers. fixation was 68.8%, while the rate of those who had no knowledge on plastination was 47.4%.…”
Section: Discussionmentioning
confidence: 92%